A 20‐year follow‐up survey of police officers' experience with Tarasoff warnings: How law enforcement reacts to clinicians' duty to protect. (22nd February 2022) - Guina, Jeffrey; Dornfeld, Bradleigh; Pinals, Debra A.
Abstract: Since the Tarasoff case of 1976, mental health professionals are recognized to have a "duty to protect" third‐party targets from violence‐threatening patients, but little is known about what happens after clinicians warn law enforcement. In 2000, Huber et al. published a study that surveyed Michigan police about "Tarasoff warnings." We conducted a 20‐year follow‐up study, inviting all Michigan police and sheriff departments to participate. There were no significant differences between studies about knowledge of Tarasoff ‐related policies, which was low in both surveys. We found significant decreases in the number of officers who had ever intervened due to warning calls. Of the survey respondents, 83% supported documenting warning calls. For those who received warnings, 96% followed up with at least one intervention. In both studies, notifying other officers was the most common action taken. 56% said they would take action to remove a firearm. We identified opportunities for training law enforcement.